2020
DOI: 10.1101/2020.08.28.20183814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-to-Host Airborne Transmission As a Multiphase Flow Problem For Science-Based Social Distance Guidelines

Abstract: COVID-19 pandemic has strikingly demonstrated how important it is to develop fundamental knowledge related to generation, transport and inhalation of pathogen-laden droplets and their subsequent possible fate as airborne particles, or aerosols, in the context of human to human transmission. It is also increasingly clear that airborne transmission is an important contributor to rapid spreading of the disease. In this paper, we discuss the processes of droplet generation by exhalation, their potential transforma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 116 publications
(201 reference statements)
0
4
0
Order By: Relevance
“…Bourouiba et al illustrated that, depending on the patient’s physiological composition (droplets of mucosalivary liquid emissions associated with hot and moist air) and meteorological conditions (humidity and temperature), the gas cloud and its payload of pathogen-bearing droplets in any size can be transmitted up to 8 m [ 64 ]. Along the way, droplets of any size can settle out or evaporate at rates that depend not only on their size but also on the degree of turbulence and velocity of the gas cloud, along with the properties of the ambient environment (temperature, humidity, and air flow) [ 64 , 65 , 66 ]. Chong et al reported that smaller respiratory droplets (<10 µm) have the tendency to be taken via the turbulent puff and travel together with the fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bourouiba et al illustrated that, depending on the patient’s physiological composition (droplets of mucosalivary liquid emissions associated with hot and moist air) and meteorological conditions (humidity and temperature), the gas cloud and its payload of pathogen-bearing droplets in any size can be transmitted up to 8 m [ 64 ]. Along the way, droplets of any size can settle out or evaporate at rates that depend not only on their size but also on the degree of turbulence and velocity of the gas cloud, along with the properties of the ambient environment (temperature, humidity, and air flow) [ 64 , 65 , 66 ]. Chong et al reported that smaller respiratory droplets (<10 µm) have the tendency to be taken via the turbulent puff and travel together with the fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Fiorillo et al suggested that health care workers must be protected from the contact with the patient’s aerosol with filtering facepiece particles masks (FFP) of type FFP2 and FFP3 [ 74 ] of similar performance to N95 and N99 masks in the United States, respectively. In the case of surgical mask, their filtration efficiency only protects the user against droplet nuclei of size larger than 2 μm [ 65 ]. In general, face coverings are more effective for decreasing the direct ejection of breath and bioaerosols away from the user [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stronger and stronger evidence suggest that the respiratory particles emitted during a sneeze or cough are initially transported as a turbulent cloud that consists of hot and moist exhaled air and mucosalivary filaments [13, 14]. Numerical simulations and analytic studies show that aerosols and small droplets trapped inside the turbulent puff cloud could propagate up to 7 or 8 m [1518]. Besides, once the cloud slows down sufficiently, and its coherence is lost, the eventual spreading of the infected aerosols becomes dependent on the ambient air currents and turbulence.…”
Section: Figmentioning
confidence: 99%
“…Surprisingly, little is known on long-time dispersion and transmission pattern of suspended viral particles in indoor environment. Such physical process of spreading is subtle as it involves interactions between respiratory droplets, turbulent eddies, vapor and temperature fields (1,28,(35)(36)(37)(38)(39), and also relates to several environmental factors such as ventilation (40)(41)(42)(43), ambient temperature (44,45) and relative humidity (46)(47)(48)(49)(50). In practice, ventilation is considered as an active control strategy to transport and exhaust those viral aerosols or droplets.…”
Section: Introductionmentioning
confidence: 99%